2016
DOI: 10.3892/or.2016.4900
|View full text |Cite
|
Sign up to set email alerts
|

LKB1 expression reverses the tumorigenicity of L02 cells

Abstract: Abstract. The tumor-suppressor liver kinase B1 (LKB1), a highly conserved and ubiquitously expressed protein kinase, plays a critical role in tumorigenesis. In the present study, we revealed that human hepatic L02 cells had severely impaired endogenous LKB1 expression as gauged by western blot, northern blot and RT-PCR analyses. Stable ectopic expression of LKB1 in L02 cells resulted in decreased cell growth, hypophosphorylation of Rb, and marked attenuation of colony formation on soft agar. Inoculation of L02… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…The results from the in vitro assays demonstrated that CACYBP overexpression had no significant effect on the proliferation and colony formation abilities in SK-Hep-1 cells, but promoted these growth abilities in LO2 cells (Figure S2B-D). LO2 is a non-cancerous hepatic cell line, although some reported that LO2 itself could form xenograft tumors in nude mice 29, 30. However, we observed no tumor formation even at month 2 after subcutaneously injecting either LO2 control or CACYBP-overexpressing cells into NSI mice (data not shown).…”
Section: Resultsmentioning
confidence: 54%
“…The results from the in vitro assays demonstrated that CACYBP overexpression had no significant effect on the proliferation and colony formation abilities in SK-Hep-1 cells, but promoted these growth abilities in LO2 cells (Figure S2B-D). LO2 is a non-cancerous hepatic cell line, although some reported that LO2 itself could form xenograft tumors in nude mice 29, 30. However, we observed no tumor formation even at month 2 after subcutaneously injecting either LO2 control or CACYBP-overexpressing cells into NSI mice (data not shown).…”
Section: Resultsmentioning
confidence: 54%
“…The human hepatic cell line LO2 was derived from primary normal human hepatocytes and has been widely applied in human hepatocellular function studies, particularly those related to drug hepatotoxicity ( 15 , 16 ). LO2 cell line was cultivated in 1640 medium with 1% penicillin (100 units/mL)/streptomycin (100 μg/mL) and 10% FBS at 37°C in a humidified atmosphere (95%) containing 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The human hepatocellular carcinoma L02 cell line was used, as it has been previously reported to express high levels of hepatic CYPs, following exposure to prototypical chemical inducers [18,21,22]. L02 cells were treated with low (10 -4 μmol/L), middle (10 -3 μmol/L), and high (10 -2 μmol/L) concentrations of muscone for 48 h and the protein was extracted as described in the Materials and Methods section.…”
Section: Resultsmentioning
confidence: 99%